2020
DOI: 10.3390/app11010287
|View full text |Cite
|
Sign up to set email alerts
|

Portable Raman Spectrometer for In Situ Analysis of Asbestos and Fibrous Minerals

Abstract: Asbestos inhalation is associated with fatal respiratory diseases and raises concerns from the perspective of workplace safety and environmental impacts. Asbestos and asbestos-like minerals naturally occur in rocks and may become airborne when outcrops or soils are disturbed by anthropic activities. In situ detection of these minerals is a crucial step for the risk evaluation of natural sites. We assess here whether a portable Raman spectrometer (pRS) may be used in the identification of asbestos and asbestos-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…The distinctive OH stretching bands with its strongest peak at 3569 cm −1 and other contributions at 3508, 3619, 3644, and 3717 cm −1 confirmed the discrimination of balangeroite among the other fibrous phases. [ 26,57 ] Weak features from chrysotile fibers are generally detected together with those of balangeroite, due to their similar structure (as marked with the symbol * in Figure 3a,b). In balangeroite, the presence of Fe as a constitutive element is confirmed by the EDS spectrum (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…The distinctive OH stretching bands with its strongest peak at 3569 cm −1 and other contributions at 3508, 3619, 3644, and 3717 cm −1 confirmed the discrimination of balangeroite among the other fibrous phases. [ 26,57 ] Weak features from chrysotile fibers are generally detected together with those of balangeroite, due to their similar structure (as marked with the symbol * in Figure 3a,b). In balangeroite, the presence of Fe as a constitutive element is confirmed by the EDS spectrum (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…A portable Raman spectrometer for the in situ analysis of asbestos was also reported. 10) Our recent study demonstrated that dyeing the surface of building waste materials with an aqueous solution of inexpensive and safe methylene blue and then dyeing it with an aqueous solution of red no. 3 (erythrosine), which is commercially available as a low-cost food coloring, chrysotile becomes stained by erythrosine.…”
Section: Introductionmentioning
confidence: 99%